Hearing loss and middle ear involvement in rheumatoid arthritis - GÜNDÜZ, OSMAN HAKAN (SPRINGER-VERLAG, 2002)
In this controlled study, hearing and middle ear functions were investigated in 37 patients with rheumatoid arthritis (RA) and 35 controls in order to study the prevalence and the nature of hearing loss in RA. The prevalence of the hearing impairment was significantly higher in the RA group, and the majority was bilateral (P<0.001). Of the patients, 35.1% had sensorineural (SN). 24.3% had conductive loss, and 10.8% had a mixed type of hearing loss. The hearing loss was positively correlated to the Steinbrocker functional index. The prevalence of abnormal tymparlograms was 37.8%, while it was 17.1% in the control group. The probable site of involvement responsible for the SN loss was the cochlea, and discontinuity of the ossicles, rather than stiffness, was responsible for the conductive hearing loss. The presence of a mixed type of hearing loss suggested a multifocal involvement of the audiologic system in RA.
Keywords: rheumatoid arthritis; hearing impairment; middle ear; ear ossicles